Process safety information, hazard control, and communication - Shariff, A.M. (Elsevier, 2020)
Avoidance of accidents in present process industries is a challenging task, therefore, process safety management (PSM) guidelines and regulations have been induced for safer operation and the compliance to PSM is considered as a key factor to avoid accidents. The PSM system is composed of number of elements, and process safety information (PSI) element has a crucial role in the successful implementation of PSM. There are three components of this element namely process chemicals, process technology and process equipment, and information regarding each component must be available. In this chapter, PSM, the PSM elements in various countries, and the components of PSI element are discussed initially. Next, the framework for PSI implementation based upon the OSHA 29 CFR 1910.119 (d) is discussed. Human interaction has a crucial role toward PSM and specifically to the PSI element, for that reason, the human errors pertinent to PSI element, specifically for each of its component, have been presented. The efficient handling of human errors may lead to a successful PSM system ultimately reducing the accidents. In this context, detailed research work is recommended to propose tools to be aligned with industry 4.0 concept for the management of PSI element by reducing human errors. Â© 2021 Elsevier Inc. All rights reserved.